Interaction of the judiciary with the institutions of legal assistance and mediation - Ablaeva, Э.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article analyzes the relationship of the judiciary with the institutions of legal assistance and mediation, such as advocacy, legal advice, notaries, and mediation. The relevance of the study increases with the development of the ideas of the concept of restorative and preventive justice, characterized by the use of extrajudicial methods of resolving cases and disputes, as well as preventive measures to prevent illegal actions. It is indicated that these methods serve as a supplement to the traditional justice administered by the courts, involving lawyers, legal consultants, mediators, and notaries in the process of settling cases and disputes, contributing to an increase in the level of legal culture of the population and the effectiveness of justice. The author studied forms of interaction between the judiciary and the institutions of legal assistance and mediation. The article reveals spheres of interaction between courts and extrajudicial bodies. It also notes positive aspects of mutual cooperation of judicial and non-judicial bodies in the protection of the rights, freedoms, and legitimate interests of citizens and organizations. Based on the results of the study, the author gives conclusions and recommendations.